2018
DOI: 10.3390/cancers10080255
|View full text |Cite
|
Sign up to set email alerts
|

Viability Assessment Following Anticancer Treatment Requires Single-Cell Visualization

Abstract: A subset of cells within solid tumors become highly enlarged and enter a state of dormancy (sustained proliferation arrest) in response to anticancer treatment. Although dormant cancer cells might be scored as “dead” in conventional preclinical assays, they remain viable, secrete growth-promoting factors, and can give rise to progeny with stem cell-like properties. Furthermore, cancer cells exhibiting features of apoptosis (e.g., caspase-3 activation) following genotoxic stress can undergo a reversal process c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 56 publications
0
31
0
1
Order By: Relevance
“…The formation of PGCCs following treatment with anticancer agents is not an infrequent response [25][26][27][28][29][30], and their frequency can be influenced by heterogeneous environment and chemotherapeutic drug gradient, increasing remarkably at high drug concentrations [25]. Given that PGCCs cease to proliferate or proliferate at a very slow rate, they are often overlooked or misrepresented as "dead" in the conventional pre-clinical assays that are performed with cultured cells or animal models (reviewed in [31,32]). However, over 60 years ago Puck and Marcus [33] reported that PGCCs (originally called giant cells), arising in cervical carcinoma (HeLa) cell cultures following exposure to ionizing radiation, remain viable and secrete growth-promoting factors.…”
Section: Multinucleated/polyploid Cancer Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of PGCCs following treatment with anticancer agents is not an infrequent response [25][26][27][28][29][30], and their frequency can be influenced by heterogeneous environment and chemotherapeutic drug gradient, increasing remarkably at high drug concentrations [25]. Given that PGCCs cease to proliferate or proliferate at a very slow rate, they are often overlooked or misrepresented as "dead" in the conventional pre-clinical assays that are performed with cultured cells or animal models (reviewed in [31,32]). However, over 60 years ago Puck and Marcus [33] reported that PGCCs (originally called giant cells), arising in cervical carcinoma (HeLa) cell cultures following exposure to ionizing radiation, remain viable and secrete growth-promoting factors.…”
Section: Multinucleated/polyploid Cancer Cellsmentioning
confidence: 99%
“…A step towards reaching this goal will be to understand not only the bright sides of different stress-induced responses (e.g., senescence) that might impact on the initial tumor control, but also their dark sides that might contribute to tumor repopulation. In addition, as cautioned by the Nomenclature Committee on Cell Death [155] and others [32,156,157], it is crucial to use the available tools (e.g., cell-based assays) in the right contexts to avoid generating misleading information. To this end, as discussed below, the colony formation and multiwell plate colorimetric/fluorometric assays predominantly determine the ability of a genotoxic agent to convert "dangerous" (proliferating) cancer cells to "even more dangerous" (e.g., dormant) cancer cells, rather than dead cancer cells.…”
Section: Can Cancer Recurrence Be Prevented?mentioning
confidence: 99%
See 1 more Smart Citation
“…In the current work we used standard molecular and cellular features of apoptosis. However, it is now well known that cells triggered to undergo apoptosis can recover from brink of death through a process called anastasis [59]. Therefore, to what extent the responses reported herein reflect death remains to be determined.…”
Section: Discussionmentioning
confidence: 93%
“…They represent rare single cells undergoing reprogramming and complex multi-step, reversible ploidy cycles, which are experimentally observed over a period of weeks. Although these rare "statistical outliers" present serious methodical difficulties for following and fate-mapping, making studies of their nature and genesis complex, they are apparently the major mediators of anti-cancer therapy resistance responsible for relapse [85].…”
Section: Discussionmentioning
confidence: 99%